Capsule retention related to small bowel capsule endoscopy: a large European single‐center 10‐year clinical experience. Issue 5 (1st August 2017) - Nemeth, Artur; Wurm Johansson, Gabriele; Nielsen, Jörgen; Thorlacius, Henrik; Toth, Ervin
Abstract : Background: The most concerning complication of video capsule endoscopy (VCE) is capsule retention (CR) in the gastrointestinal (GI) tract although clinical outcome and management of patients with CR are still uncertain in a large single center material. Objectives: The aim of this retrospective study was to investigate incidence, causes, risk factors, management and clinical outcomes of CR in a large single center between 2001 and 2011. Results: 2401 consecutive small‐bowel (SB) VCEs were performed. CR was detected in 25 cases (1%). CR in patients with suspected and known Crohn's disease (CD) undergoing VCE occurred in 14/1370 (1%) including known CD 9/390 (2.3%) and suspected CD 5/980 (0.5%). CR in patients with obscure GI bleeding was observed in 11/816 (1.3%) cases. The SB was the most common site of CR with 17 cases followed by the esophagus (4 cases), colon (2 cases), and stomach (2 cases). Emergency endoscopic intervention (3 cases) and surgery (2 cases) was needed in 5 cases of CR. Elective capsule removal was performed by surgery in 6 cases and endoscopically in 8 cases. Three retained capsules dislodged after steroid treatment and another 3 cases of CR resolved without any intervention. Conclusion: This large clinical material demonstrates that CR is a rare complication with a favorable clinical outcome. Most patients with CR can be electively managed with non‐surgical intervention.